COVARYING COLLEXEME ANALYSIS AS A TYPE OF COLLOSTRUCTIONAL ANALYSIS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article introduces the concept of Covarying Collexeme Analysis (CCA), a novel approach for examining the relationships between linguistic forms and their contextual usages. CCA enhances traditional collexeme analysis by considering contextual variability, allowing for the identification of co-occurrence patterns between specific lexical items and their grammatical constructions. Through empirical studies, we illustrate how CCA can reveal underlying semantic and syntactic trends that enhance our understanding of language use. By applying this method to various corpora, we emphasize its effectiveness in identifying both common collocations and the subtle interactions that influence meaning in discourse. Our findings indicate that CCA provides a valuable framework for linguists to explore the dynamic relationship between language form and function, ultimately enriching our understanding of linguistic structures and their cognitive foundations.